Endothelial cell spheroids as a versatile tool to study angiogenesis in vitro - Heiss, Maximilian; Hecker, Markus; Augustin, Hellmut; Korff, Thomas (The FASEB journal, 2015)
Given the need for robust and cost-efficient in vitro models to study angiogenesis and reproducibly analyze potential pro- and antiangiogenic compounds in preclinical studies, we developed a 3-dimensional in vitro angiogenesis assay that is based on collagen gel-embedded, size-defined spheroids generated from cultured human umbilical vein endothelial cells (HUVECs). Despite its wide distribution, limitations, sensitivity, robustness, and improvements, the capacity of this assay for functional screening purposes has not been elucidated thus far. By using time-lapse video microscopy, we show that tip cells lead the formation of capillary-like and partially lumenized sprouts originating from the spheroids. Angiogenic sprouting from spheroids generated from 5 different primary cultured human endothelial cell types was induced by physiologic concentrations of vascular endothelial cell growth factor 165. Based on this assay system, we determined the capacity of 880 approved drugs to interfere with or boost angiogenic sprouting, thereby assessing their putative angiogenesis-related side effects or novel applications. However, although this assay allowed for a rapid and reproducible determination of functional IC50 values of individual compounds, the sprouting results were partially affected by the HUVEC passage number and donor variability. To overcome this limitation, immortalized HUVECs (iHUVECs) showing a more homogenous response in terms of proliferation and sprouting over multiple population doublings were used in the course of this study. Collectively, the spheroid-based angiogenesis assay provides a sensitive and versatile tool to study the impact of pro- and antiangiogenic determinants on multiple steps of the angiogenic cascade. It is compatible with different endothelial cell types and allows use of iHUVECs to improve its overall robustness.